COVID-19 and mental health in Brazil: Psychiatric symptoms in the general population - Goularte, Jeferson Ferraz; Serafim, Silvia Dubou; Colombo, Rafael; Hogg, Bridget; Caldieraro, Marco Antonio; Rosa, Adriane Ribeiro (Journal of psychiatric research, 2021)
Public health interventions at general population level are imperative in order to decrease the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but they may contribute to widespread emotional distress and increased risk for psychiatric illnesses. We report on the results of an investigation into the occurrence and determinants of psychiatric symptoms among the Brazilian general population (N = 1996). We assessed sociodemographic variables and general mental health (DSM-5 Self-Rated Level 1 Cross-Cutting Symptom Measure), depression (PROMIS depression v.8a), anxiety (PROMIS anxiety v.8a), and post-traumatic stress symptoms (Impact of Event Scale-IES-R scale) using an online web-based survey. Anxiety (81.9%), depression (68%), anger (64.5%), somatic symptoms (62.6%) and sleep problems (55.3%) were the most common psychiatric symptoms. Younger age, female gender, low income, lower level of education, longer period of social distancing, and self-reported history of previous psychiatric illness were strongly associated with higher severity of symptoms. Our results support the negative impact of the COVID-19 pandemic on the mental health of the Brazilian population. The high prevalence of psychiatric symptoms observed in our sample indicates that the mental health impact of the COVID-19 pandemic should be considered a public health problem in Brazil. The health systems and individual clinicians must be prepared to offer and implement specific interventions in order to identify and treat psychiatric issues.